2011
DOI: 10.1002/qua.23280
|View full text |Cite
|
Sign up to set email alerts
|

Computational study of the patterns of weaker intramolecular hydrogen bonds stabilizing acylphloroglucinols

Abstract: Acylphloroglucinols (ACPLs) are polyphenolic compounds derivative from phloroglucinol, characterized by the presence of at least one COR group and exhibiting a variety of biological activities, which makes them interesting for drug development possibilities. This study investigates patterns in the ways in which weaker intramolecular hydrogen bonds contribute to their conformational stabilization, considering the CH···O H‐bonds, present in all ACPLs, and the OH···π H‐bonds, present in ACPLs in which one or mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 26 publications
1
29
0
Order By: Relevance
“…In a similar manner, the para substituted OH group (O4H4) in ring B can interact with neighbouring O3 to form an IHB, here called the second H-bond and denoted as HB2. IHBs are known to stabilise conformations [47][48][49][50][51][52][53][54][55] as well as to influence the biological activities of compounds, such as antioxidant activity [24,25,32,34].…”
Section: Introductionmentioning
confidence: 99%
“…In a similar manner, the para substituted OH group (O4H4) in ring B can interact with neighbouring O3 to form an IHB, here called the second H-bond and denoted as HB2. IHBs are known to stabilise conformations [47][48][49][50][51][52][53][54][55] as well as to influence the biological activities of compounds, such as antioxidant activity [24,25,32,34].…”
Section: Introductionmentioning
confidence: 99%
“…Calculations were performed with the same levels of theory as in previous studies of ACPLs [ 7 , 8 , 9 , 10 , 11 ], to enable informative comparisons: Hartree Fock (HF) with the 6-31G(d,p) basis set and Density Functional Theory (DFT) with the B3LYP functional and the 6-31+G(d,p) basis set, both with fully relaxed geometry, and MP2 single-point (SP) calculations on the HF-optimised conformers. The general studies of ACPLs [ 7 , 8 , 9 , 10 , 11 ] had shown that HF gives reasonable results for this class of compounds and enables realistic trend-identifications with the reasonably cheap 6-31G(d,p) basis set.…”
Section: Computational Detailsmentioning
confidence: 99%
“…ACPLs [ 6 ] are derivatives of phloroglucinol (1,3,5-trihydroxybenzene) characterised by the presence of a COR group (acyl group), whose sp 2 O can form an intramolecular hydrogen bond (IHB) with one of the two ortho OHs; following a practice introduced in previous works on ACPLs [ 7 , 8 , 9 , 10 , 11 ], this IHB (which is present in nearly all ACPLs) is here termed ‘first IHB’. In arzanol, R is a methyl group; an α-pyrone ring is attached to one position meta to the COR group (C3) and a prenyl chain is attached to the other meta position (C5).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations